ANALISIS IMPLEMENTASI SAK-EMKM DALAM MENINGKATKAN TRANSPARANSI KEUANGAN PADA UMKM SEKTOR PERDAGANGAN DI TANGERANG SELATAN - Hendra Candra; Syarif Hidayatullah (Laboratorium Riset Ekonomi, 2024)
SAK-EMKM has been introduced as an effort to increase financial transparency and make it easier for micro business owners to manage their finances. This study aims to conduct an in-depth analysis of the implementation of SAK-EMKM and its impact on financial transparency in micro enterprises in the trade sector. This study uses a qualitative descriptive approach with a thematic analysis method. The population in this study is 27 MSME traders and the sample that is worthy of research is 8 samples. The data collection uses observation, interview and documentation techniques. The result of this study is that 7 out of 8 MSME traders do not refer to SAK-EMKM so they experience several obstacles including transparency of financial statements, financing and taxation. While 1 sample, the financial report has referred to SAK-EMKM so that the sample has benefited because the financial report is more transparent, clear and detailed when you want to know the profit and loss, debts and receivables, inventory of goods and others.